Rate of Incidental Parathyroidectomy in a Pediatric Population. Issue 4 (November 2021) - Sahyouni, Grace; Osterbauer, Beth; Park, Soyun; Paik, Connie; Austin, Juliana; Gomez, Gabriel; Kwon, Daniel
Objective: Incidental parathyroidectomy is a relatively common occurrence in thyroid surgery, which may lead to hypoparathyroidism and postoperative hypocalcemia, but it is not well studied in children. The objectives of this study were to determine the rate of incidental parathyroidectomy, identify potential risk factors, and investigate postoperative complications in children undergoing thyroidectomy. Study Design: Retrospective cohort study. Setting: Patients who underwent thyroidectomy over a 10-year period at a tertiary children's hospital. Methods: Pathology reports were reviewed to determine incidental parathyroid gland tissue. Additional data collected included patient demographics, type of procedure, underlying thyroid pathology, as well as immediate and long-term postoperative clinical outcomes. Results: Of 209 patients, 65 (31%) had incidental parathyroidectomy. Several variables were associated with incidental parathyroidectomy on univariable analysis. However, in the final multivariable model, only thyroidectomy with lymph node dissection was associated with increased odds of having incidental parathyroidectomy (odds ratio, 3.3; P = .04; 95% CI, 1.1-9.8). After a median follow up of 1 year, a significantly higher percentage of patients with incidental parathyroidectomy had evidence of long-term hypoparathyroidism (9/62 [15%] vs 3/144 [2%], P = .001). Conclusion: Incidental parathyroidectomy was relatively common in our pediatric thyroidectomy population, which may be a result of several anatomic, clinical, and surgeon-related factors. Close attention to parathyroid preservation with meticulous surgical technique is the most practical method of preventing long-term hypoparathyroidism and hypocalcemia.